Male rat hormone imbalance, testicular changes and toxicity associated with aqueous leaf extract of an antimalarial plant: Phyllanthus niruri. (June 2013) - Asare, George Awuku; Bugyei, Kwasi; Fiawoyi, Irene; Asiedu-Gyekye, Isaac Julius; Gyan, Ben; Adjei, Samuel; Addo, Phyllis; Otu-Nyarko, Lydia; Nyarko, Alexander
Abstract Context: Phyllanthus niruri L. (Euphorbiaceae), a medicinal plant traditionally known for dissolving kidney stones, is used prophylactically as an antimalarial agent. Objective: The study was undertaken to determine its effect on some male hormones and other toxicological properties due to paucity of its data despite its wide use. Material and methods: Male Sprague–Dawley rats (100–140 g) were used. Group 1 [control group (C), n = 6] received water. Group 2 [low-dose test group (LD), n = 6] received 50 mg/kg body weight (b.wt.) aqueous leaf extract orally. Group 3 [high-dose test group (HD), n = 6] received 500 mg/kg b.wt. extract for 90 days. Upon sacrifice, among other organs the testes were harvested. Blood samples drawn were used for biochemical (including progesterone, estrogen and testosterone), cytotoxicity and hematological assays. Results: C, LD and HD estrogen values were 192 ± 25, 385 ± 122 and 962 ± 357 pg/ml, respectively. In the same order, progesterone values were 96 ± 24, 155 ± 45 and 320 ± 80 pg/ml, respectively. Testosterone levels were 5210 ± 1090, 4710 ± 220 and 4500 ± 580 pg/ml, respectively. Significant differences were observed in the estrogen and progesterone levels (p = 0.001). Degenerative changes were observed histologically. Cytotoxicity at 50% (CC50) was 10.0 µg/ml. Discussion and conclusion: This antimalarial plant is mildly cytotoxic with male antifertility properties.